Sport, Religion and Charisma. Issue 1 (2nd January 2017) - Møller, Verner
Abstract: Since the end of the Second World War, the popularity of modern elite sport has grown immensely and so has the economical interests in sport. Athletes have become attractive advertising partners. Much money is at stake so it is understandable that companies are alarmed when their poster boys or girls are caught up in scandals. Inspired by a recent study, which found that stock return of primary team sponsors in cycling was not affected if the team was involved in doping scandals, this paper is an attempt to explain why athletes often maintain their marketing value even if they are exposed as bad role models. The thesis is that the attraction of athletes relates to the concept of 'charisma', and that the success of mass spectator sports is due to sport's appeal to what psychologist Henry Rutgers Marshall by the end of the 19th Century in an article in Mind identified as man's 'religious instinct'. So after a brief introduction, the paper begins with a clarification of the antiquated concept 'religious instinct'. This is followed by a critical examination of the secular usage of 'charisma' as introduced by Max Weber. Peter Sloterdijk's sobering point that Hitler's aptitude for his role in Germany did not rely on charisma lays the foundation for a more precise and rationally consistent description of the concept. It is argued that charisma is not something certain individuals posses, rather it is something that is experienced as an emotional effect by those who label individuals charismatic, which is based on the honesty competence and commitment of the perceived 'charismatic' person. Idols can have charismatic effect on us even if they are unprincipled cheats so long as they are committed to what they do. This is why athletes maintain their appeal and marketing value so long as their performances transcend the capabilities of ordinary people.